Determinants of Dividend Policy and Their Implications for Firm Value Using the Signaling Model - Putri, Nadia Ayuni; Hitten, Akhmad; Heniwati, Elok (APSSAI ACCOUNTING REVIEW, 2024)
Research aims: This study aims to analyze the effect of profitability, capital structure,      and free cash flow on company value, with dividend policy as an intervening variable in banking companies. Design/Methodology/Approach: The research uses secondary data obtained from banking companies listed on the Indonesia Stock Exchange for the period 2014-2020. A total of 45 companies constituted the population, and purposive sampling was used to select 19 companies that met the criteria for testing. Data analysis was conducted using the Partial Least Square (PLS) method with the SmartPLS version 3.2.8 software. Research findings: The results revealed that profitability has a significant positive effect on dividend policy, while capital structure has no effect on dividend policy. Free cash flow, on the other hand, shows a significant positive effect on dividend policy. Furthermore, profitability has a significant positive effect on company value, and capital structure also positively and significantly affects company value. However, free cash flow has no effect on company value, and dividend policy does not influence company value.   Theoretical contribution/Originality: This research contributes to the understanding of the dynamics between profitability, capital structure, free cash flow, dividend policy, and company value, particularly within the context of the banking sector. Practitioner/Policy implication: The findings provide insights for practitioners and policymakers in banking companies to better align profitability and dividend policy to enhance company value. Research limitation/Implication: The study is limited to banking companies listed on the Indonesia Stock Exchange during 2014-2020 and may not generalize to other sectors or time periods.